Increased ice losses from Antarctica detected by CryoSat‐2. Issue 11 (9th June 2014) - McMillan, Malcolm; Shepherd, Andrew; Sundal, Aud; Briggs, Kate; Muir, Alan; Ridout, Andrew; Hogg, Anna; Wingham, Duncan
Abstract We use 3 years of Cryosat‐2 radar altimeter data to develop the first comprehensive assessment of Antarctic ice sheet elevation change. This new data set provides near‐continuous (96%) coverage of the entire continent, extending to within 215 km of the South Pole and leading to a fivefold increase in the sampling of coastal regions where the vast majority of all ice losses occur. Between 2010 and 2013, West Antarctica, East Antarctica, and the Antarctic Peninsula changed in mass by −134 ± 27, −3 ± 36, and −23 ± 18 Gt yr−1, respectively. In West Antarctica, signals of imbalance are present in areas that were poorly surveyed by past missions, contributing additional losses that bring altimeter observations closer to estimates based on other geodetic techniques. However, the average rate of ice thinning in West Antarctica has also continued to rise, and mass losses from this sector are now 31% greater than over the period 2005–2010.